The Effectiveness of Practice Genre Based Approach (PGBA) in Enhancing Students' English Essay Writing Proficiency to College Classroom Contexts - Harpiansi, Harpiansi (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
The purpose of the study was to determine whether the ability of the fourth semester students of accounting program of Politeknik Sekayu in writing English essays through Process Genre-Based Approach (PGBA) increase. The design of this experiment method research was pre-experimental-one group pretest posttest. The population was semester IV (even) students for the academic year 2022/2023. Total sampling technique was applied. Data collection techniques were carried out using pretest and post-test. The treatment was carried out 6 times. The results of the data were analyzed statistically. The results showed that the posttest average score (70.7) was higher than the pretest average (55.67). This showed that the semester students' ability to write English essays through the Application of the Process Genre-Based Approach (PGBA) increased. The results of this study were very useful for: (1) students to improve their essay writing skills; (2) teachers (lecturers) to add an approach to learning to write essays through PGBA with (a) preparation stages; (b) modeling and reinforcing; (c) planning; (d) joint construction; (e) independent constructing; and (f) revising. (3) English lecturers and teachers can conduct classroom action research using PGBA.